Delivery of glucocorticoid conjugate in rat gastrointestinal tract and its treatment for ulcerative colitis - Zhou Si-Yuan; Mei Qi-Bing; Liu Li; Guo Xin; Qiu Bo-Sheng; Zhao De-Hua; Cho Chi-Hin (Acta Pharmacologica Sinica; Vol 22, No 8 (August 2001): Acta Pharmacologica Sinica, 2016)
Aim: To evaluate colonic delivery and therapeutic effect of the newly synthesized dexamethasone (DX)-dextran (500 000) conjugate (DXD50) in the rat. Methods: The amount of dexamethasone was measured in the contents from different parts of rat gastrointestinal tract and in plasma after ig conjugate. Therapeutic effect of conjugate and DX was tested in trinitrobenzenesulfonic acid-induced colitis in rat. Repair of colitis was assessed by measuring colonic ulceration area, colon weight, and colonic myeloperoxidase (MPO) activity. Systemic immunosuppression of DX was evaluated with weight of thymus and spleen and lymphocyte count in peripheral blood from rat with ulcerative colitis. Results: Dexamethasone released from conjugate was mainly distributed in contents of cecum and colon. When DXD50 and DX 0.25 micromol . kg-1 . d-1 were used ig to treat ulcerative colitis in rat, the ulcerative area of colon was reduced by 55.6 % and 33.3 %, respectively whereas colon weight was reduced by 17.9 % and 2.6 %, respectively. The conjugate had no effect on lymphocyte count in peripheral blood, spleen weight, and thymus weight of rat which could be reduced markedly by the same dose of DX (P < 0.05 vs control). Conclusion: DXD50, which could specifically deliver DX to large intestine, is a promising agent in the treatment of human inflammatory bowel disease.